Soluble and Supported Molecular CoIII Catalysts for the Regioselective Ring‐Opening of 1, 2‐Epoxyhexane with Methanol. Issue 1 (12th November 2012) - Venkatasubbaiah, Krishnan; Feng, Yan; Arrowood, Tina; Nickias, Peter; Jones, Christopher W.
Abstract The regioselective ring‐opening of 1, 2‐epoxyhexane with methanol as a nucleophile is studied using an array of different molecular CoIII catalysts, specifically trans‐CoIII‐salen‐X (1‐X; X=Cl−, OTs−, BF4−, SbF6−, PF6−), cis/trans‐CoIII‐salen‐SbF6, CoIII‐salphen‐SbF6, and CoIII‐porphyrin‐SbF6. Catalytic studies show the nature of the ligand and counterion both play a significant role in influencing reaction rates, and to a lesser extent, the regioselectivity of the ring‐opening reaction, with CoIII‐porphyrin‐SbF6 as the most active and CoIII‐salphen‐SbF6 the least active soluble molecular catalysts. Unlike in the classical epoxide hydrolytic kinetic resolution reaction, non‐coordinating, non‐nucleophilic counterions proved most effective, and trans‐CoIII‐salen‐Cl, which gives very high initial rates in hydrolytic kinetic resolution, shows very low activity in epoxide ring‐opening with methanol. Supported soluble and insoluble unsymmetrical trans‐CoIII‐salen‐X catalysts are, thus, synthesized to evaluate cooperativity and stability of the CoIII‐salen species towards epoxide ring‐opening with methanol. Soluble supported trans‐CoIII‐salen‐X (X=SbF6 and OTs) shows better activity and selectivity in the title reaction than monomeric trans‐CoIII‐salen‐SbF6 catalyst because of the cooperativity introduced through the catalyst design. The stability of insoluble catalysts is evaluated by catalytic recycling experiments. The supported insoluble catalysts successfully are recovered and reused up to 5 times, showing reduced activity but unchanged selectivity after each cycle. Deactivation is attributed to several different causes based on elemental analysis and UV/Vis spectroscopic analysis of the used catalysts, with counterion and cobalt loss playing major roles.